Here Today, Gone Tomorrow? Changes in 4-Month-Olds' Physiologic and Behavioral Responses Do Not Indicate Memory for a Social Stressor - DiCorcia, Jennifer A.; Snidman, Nancy C.; Tronick, Ed (Frontiers in Psychology, 2018)
Although much is known about early memory development, only a few studies have explored infants’ memory of social stress. While these few studies suggest that infants can remember stressful interactions, limitations seen in both methodology and statistical analyses give pause. In the current study, 4-month-olds and their mothers participated in both stressful and non-stressful interactions over two days. On Day 1, memory group infants participated in the double Face-to-Face Still-Face (FFSF) paradigm and control group infants participated in typical play. Both groups experienced the double FFSF paradigm on Day 2. Memory group infants exhibited the standard SF response but no differences in infant cortisol on Day 1. Both infant groups exhibited the standard SF response on Day 2. However infants in the memory group, who saw the FFSF paradigm for the second time, did not demonstrate changes in cortisol or behavior indicative of memory across the two days. There was also no relationship between changes in cortisol and behavior for both days. The findings question the use of salivary cortisol as a measure of social stress and suggest that, although 4-month-olds reacted to the still-face social stressor immediately, they did not remember the following day.